RANCANG BANGUN JARINGAN RT/RW NET DENGAN MIKROTIK - M. Andi Prio Santoso; Iman Saufik Suasana (STEKOM PRESS, 2018)
Jl Karanglo RW 03 Pedurungan Semarang is a densely populated environment, its people are very hungry for fast and accurate information. The internet is available which is relatively expensive as the main choice in finding the information needed. However, the cost is very expensive for a connection that must be paid every month. Although currently many CDMA and GSM modems available on the market are not enough to meet the need for speed of an internet connection. Although there are internet cafes established, they have not streamlined the cost and time of internet users in the area. The purpose of this study is to save the cost of bandwidth rental per month for unlimited connections, provide a stable internet connection that can be used for 24 hours straight, provide data transfer with bandwidth management, so as to better guarantee the quality of the internet connection. The system development method used is Prototyping which stages include identifying user needs, making a prototype, agreeing to the user, using a prototype. As a server, using Mikrotik Os where in Mikrotik Os there are several important and interesting features provided by Mikrotik itself, among those features are bandwidth management, firewall, DNS client chacing, and many other features provided by Mikrotik. With this Mikrotik provides stability of internet data transfer in accordance with the management of Mikrotik Os as a server. The client uses a Windows-based operating system, this is because the driver tool used is more compatible using a Windows operating system than using a Linux-based operating system, because it has to compile the driver.